Foreign investment styles and returns in Portugal's real estate market - Carvalho, Leonor Silva Garcia Ramos de (2019)
The current context of Portugal’s real estate market has become a phenomenon of great interest, which leads to the need to study some of its specificities. In fact, the market is facing an outstanding performance and foreign investors are increasing their interest in investing in properties all over Portugal. Thus, it is important to analyze what are these investors looking for and what can be done so that this positive environment can continue. For this matter, the study of investment styles arises as way to understand the profile of foreign investors. The idea of real estate as an asset has become more global and the study of investment styles will help defining new guidelines for the real estate market, so that the needs of foreign investors can meet what Portugal’s market has to offer. Consequently, the aim of the thesis is to identify the different investment styles of foreign investors in Portugal’s real estate market and discuss whether the weight of the various style impacts, or not, the market returns. It is also analyzed if the variation of volume of transaction changes the investment styles. The results demonstrate that the two key players in Portugal’s real estate market were core and value added investors. It is also concluded that there is no strong correlation between investment styles and market returns. Relatively to the volume of transactions, the results suggest that it is catalyzed by opportunistic investors meaning that they are the responsible for the growth of the market.